Pengaruh Kepemimpinan Transformasional dan Lingkungan Kerja terhadap Kinerja dengan Motivasi sebagai variabel mediasi - Desy Bella Safitri; Slamet Widodo (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This study aims to explore the influence of transformational leadership and work environment on employee performance with motivation as a mediating variable at PT. Marhum Roda Mas Abadi. This study uses a quantitative approach with interviews and questionnaires distributed to company employees as the main data collection instruments. Data analysis uses path analysis techniques with a second-order confirmatory approach to test the relationship between variables. The analysis method used is partial least squares (PLS) using the SmartPLS 4.0 program. The population consists of employees of PT. Marhum Roda Mas Abadi, while the sample for this study consists of 203 permanent employees selected using purposive sampling with the criteria of permanent employees who are directly affected by transformational leadership without involving outsourcing and manual labourers. The validity test used Average Variance Extracted (AVE) and the reliability test was conducted by calculating Cronbach's Alpha and Composite Reliability (CR) values. This study shows that transformational leadership and work environment have a positive effect on performance, and transformational leadership and work environment also affect motivation. This study provides evidence that there is a mediating role of Motivation in the relationship between Transformational Leadership, Work Environment and Performance.